Increasing Knowledge About History of Hindu Empire in Indonesia with Game “Indo Trivia” - Pieter Theodorus Handoko; Erdhi Widyarto Nugroho; Bernadinus Harnadi (Journal of Business and Technology, 2022)
Most young people think that History is not important enough to learn and they are more likely to choose to play games. This study aims to develop the game "Indo Trivia" which is a game about the history of Indonesia, especially the history of the Hindu kingdom on the island of Java. In this game, there is a history of the Tarumanegara kingdoms, Hindu Mataram, Kediri, Singasari, and Majapahit kingdoms. This thesis report contains about how to make games as a medium of learning about history, especially history during the Hindu kingdom as well as providing a quiz about the history of Indonesia. The game development method used is the waterfall. The game testing method by proposing a hypothesis that is tested using a questionnaire test tool. a questionnaire will be given if the respondent has finished playing the game "Indo Trivia". From the results of the study, it was found that the variables of convenience, usefulness, and pleasure correlated with the variable of desire to reuse.